Growth of high quality and uniformity AlGaN/GaN heterostructures on Si substrates using a single AlGaN layer with low Al composition - Cheng, Jianpeng; Yang, Xuelin; Sang, Ling; Lei Guo; Zhang, Jie; Wang, Jiaming; He, Chenguang; Zhang, Lisheng; Wang, Maojun; Xu, Fujun; Tang, Ning; Qin, Zhixin; et al. (SCIENTIFIC REPORTS, 2016)
By employing a single AlGaN layer with low Al composition, high quality and uniformity AlGaN/GaN heterostructures have been successfully grown on Si substrates by metal-organic chemical vapor deposition (MOCVD). The heterostructures exhibit a high electron mobility of 2150 cm(2)/Vs with an electron density of 9.3 x 10(12) cm(-2). The sheet resistance is 313 +/- 4 Omega/square with +/- 1.3% variation. The high uniformity is attributed to the reduced wafer bow resulting from the balance of the compressive stress induced and consumed during the growth, and the thermal tensile stress induced during the cooling down process. By a combination of theoretical calculations and in situ wafer curvature measurements, we find that the compressive stress consumed by the dislocation relaxation (similar to 1.2 GPa) is comparable to the value of the thermal tensile stress (similar to 1.4 GPa) and we should pay more attention to it during growth of GaN on Si substrates. Our results demonstrate a promising approach to simplifying the growth processes of GaN-on-Si to reduce the wafer bow and lower the cost while maintaining high material quality.